Scenario modelling of sustainable electricity pathways in Côte d’Ivoire: an open-source system framework - Toukam, Derval Olivier; Meyer, Jörg; Adam, Mario; Alsmeyer, Frank (International Journal of Sustainable Energy Planning and Management, 2026)
Côte d’Ivoire faces rapidly increasing electricity demand and persistent access inequalities while pursuing low-carbon development objectives. This paper presents a spatially explicit, scenario-based electricity system analysis using PyPSA-Earth, an open-source optimisation framework. The national power system is modelled with 14 spatial clusters and hourly resolution to assess long-term generation expansion, dispatch, and system costs for 2030, 2040, and 2050 under three internally consistent scenarios: Baseline (current policies), Policy (progressively tightening electricity-sector emission limits), and Renewables (near-zero emissions). Electricity demand increases from 12.27 TWh in 2030 to 26.74 TWh in 2050 across all scenarios. Solar photovoltaics emerge as the dominant expansion technology, while existing hydropower provides stable system flexibility. In the Baseline pathway, electricity-sector CO₂ emissions rise from 1.10 Mt in 2030 to 2.66 Mt in 2050. The Policy scenario limits CO₂ emissions to 1.05 Mt by 2050, whereas the Renewables scenario reaches zero annual emissions within the model boundary. Annualised system costs increase with demand, reaching 1,380 M EUR (Baseline), 1,291 M EUR (Policy), and 1,493 M EUR (Renewables) in 2050. The analysis demonstrates a transparent and reproducible framework for long-term electricity planning in data-constrained contexts.